Sarcopenia is negatively associated with long‐term outcomes in locally advanced rectal cancer. Issue 1 (28th August 2017) - Choi, Moon Hyung; Oh, Soon Nam; Lee, In Kyu; Oh, Seong Taek; Won, Daeyoun David
Abstract: Background: The association of sarcopenia and visceral obesity to treatment outcome is not clear for locally advanced rectal cancer. This study evaluates the influence of skeletal muscle and visceral fat on short‐term and long‐term outcomes in locally advanced rectal cancer patients treated with neoadjuvant chemoradiation therapy followed by curative resection. Methods: A total of 188 patients with locally advanced cancer were included between January 2009 and December 2013. Neoadjuvant chemoradiotherapy was followed by curative resection. Sarcopenia and visceral obesity were identified in initial staging CT by measuring the muscle and visceral fat area at the third lumbar vertebra level. Results: Among the 188 included patients, 74 (39.4%) patients were sarcopenic and 97 (51.6%) patients were viscerally obese. Sarcopenia and high levels of preoperative carcinoembryonic antigen were significant prognostic factors for overall survival ( P  = 0.013, 0.014, respectively) in the Cox regression multivariate analysis. Visceral obesity was not associated with overall survival; however, it did tend to shorten disease‐free survival ( P  = 0.079). Conclusions: Sarcopenia is negatively associated with overall survival in locally advanced rectal cancer patients who underwent neoadjuvant chemoradiation therapy and curative resection. Visceral obesity tended to shorten disease‐free survival. Future studies should be directed to optimize patient conditions according to body composition status.